2020
DOI: 10.3390/ijms21186581
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and COVID-19: Adding Fuel to the Flame

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, an infection caused by the severe acute respiratory syndrome coronavirus (SARS-CoV-2), has led to more than 771,000 deaths worldwide. Tobacco smoking is a major known risk factor for severe illness and even death from many respiratory infections. The effects of smoking on COVID-19 are currently controversial. Here, we provide an overview of the current knowledge on the effects of smoking on the clinical manifestations, disease progression, inflammatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 173 publications
(255 reference statements)
2
71
4
Order By: Relevance
“…The understanding of the relationship between COVID-19 and smoking is evolving ( CDC, 2020 ), with preliminary studies showing associations between smoking and COVID-19 infection ( Engin et al, 2020 ), progression ( Lowe et al, 2021 ), and severity ( Patanavanich and Glantz, 2020 , Paleiron et al, 2021 , Kashyap et al, 2020 ). Smokers may be more susceptible to bacterial and viral infections ( Berlin et al, 2020 ) that may be more likely to progress compared to non-smokers ( Lowe et al, 2021 , Patanavanich and Glantz, 2020 ), possibly due to older age ( Liu et al, 2020 ) and certain chronic conditions ( Engin et al, 2020 , CDC, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the relationship between COVID-19 and smoking is evolving ( CDC, 2020 ), with preliminary studies showing associations between smoking and COVID-19 infection ( Engin et al, 2020 ), progression ( Lowe et al, 2021 ), and severity ( Patanavanich and Glantz, 2020 , Paleiron et al, 2021 , Kashyap et al, 2020 ). Smokers may be more susceptible to bacterial and viral infections ( Berlin et al, 2020 ) that may be more likely to progress compared to non-smokers ( Lowe et al, 2021 , Patanavanich and Glantz, 2020 ), possibly due to older age ( Liu et al, 2020 ) and certain chronic conditions ( Engin et al, 2020 , CDC, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has been reported that long term smokers express high levels of ACE2 receptor ( 78 ), namely in type-2 pneumocytes and alveolar macrophages ( 79 ), making them at high risk of infection by SARS-CoV-2 ( 78 ). This elevated expression occurs through activation of the α7 subtype of the nicotine acetylcholine receptor (α7-nAChR) ( 80 ).…”
Section: Differential Response To Covid-19 Could Be Related To Ace2 Ementioning
confidence: 99%
“…Despite limitations of the rapidly emerging available data, such as relying on electronic medical record data for smoking status, it is likely that combustible and non-combustible tobacco product use influences COVID-19 progression and negative health outcomes including death. Thus, a recent review concluded that smoking cessation is expected to reduce COVID-19-related risks and severe complications, and acknowledged telemedicine as one tool that can be employed to promote quitting smoking ( 36 ).…”
Section: Tobacco Use and Covid-19mentioning
confidence: 99%